Do Chronic Alcoholism Effect to The Cornea and Retina? (Alcohol and Eye) - Gunduz, Abuzer; Cumurcu, Tongabay; Cumurcu, Birgul Elbozan; Demirel, Ersin Ersan; Gül, Isil Gögcegöz; Firat, Pempegül (Journal of Ocular Diseases and Therapeutics, 2013)
Objective: To compare quantitative anterior and posterior segment data obtained with the Pentacam and OCT in individuals who are chronic users of alcohol (ethanol). Methods: Our study was a prospective, case-control study conducted on two groups. The first group (Group 1) consisted of 30 male patients who had presented at the Psychiatry outpatient department of our hospital for the treatment of alcoholism. The second group (Group 2) consisted of 30 age- and sex-matched individuals as the control group. This group included the healthy persons accompanying their relatives who had come to the Eye Department for treatment. All cases underwent an ocular examination, measurement of the axial length, Pentacam examination and Spectral Domain Optic Coherence Tomography (SD-OCT). The quantitative data from these measurements were compared between the two groups. The significance level for the tests was 0.05. Results: The mean age was 45.0±8.03 (28-59) years in the group 1 and 41.83±8.5 (31-60) years in the control group. The mean alcohol use duration was 18.33±9.94 years in group 1. There was no statistically significant difference between the two groups for age or axial length. There was also no significant difference between the groups for the Pentacam K (keratometry), CCT (central corneal thickness), ACD (anterior chamber depth), ACA(anterior chamber angle), ACV(anterior chamber volume) and LT (lens thickness) data (p>0.05). There was also no difference between the groups for the SD-OCT FCT (Foveal 1 mm central ring thickness), S-GCC (Superior-hemiretinal ganglion cells complex), I-GCC (Inferior hemiretinal ganglion cells complex), G-RNFL (Global -Retinal nerve fiber layer), I-RNFL (Inferior -Retinal nerve fiber layer), S-RNFL (Superior-Retinal nerve fiber layer), N-RNFL (Nasal-Retinal nerve fiber layer) and T-RNFL (Temporal-Retinal nerve fiber layer) data (p>0.05). Conclusion: The results of this study were not find a difference between measurements of the ocular structures of individuals with a history of chronic alcohol use and healthy individuals in this quantitative study.